Assessment of infrastructure, manpower and functioning of an anganwadi centre of an urban area of south 24 parganas, West Bengal, India - Rituraj, Dey; Rajib, Sikder; Sankha, Kundu Subha; Kanti, Majumdar Kunal; Kumar, Joardar Goutam (International Journal Of Community Medicine And Public Health, 2020)
Background: ICDS is one of the flagship programmes of the Government of India. Proper utilization of ICDS services depend on factors like infrastructure, accessibility, availability of resources and satisfaction of the beneficiaries. ICDS services are essential for promotion of health and nutritional status of mothers and adolescents; psychological, physical, social development of children. The scheme is important to reduce morbidity, mortality, malnutrition, school dropouts among the beneficiaries. To assess the overall functioning, a cross sectional study was conducted in an Anganwadi Centre of South 24 Parganas district of West Bengal. Methods: In 2019, a cross-sectional study conducted in an Anganwadi centre at Sonarpur block, South 24 Parganas, West Bengal. Out of 26 AWCs present in Sonarpur block, 1 AWC selected randomly for study. Data collected with a predesigned, pretested and structured oral questionnaire. Results: AWC was in a shared club room with adequate infrastructure. Manpower adequate. Materials and equipment’s adequate, well maintained. 91% children had available growth charts, 96% accurately plotted. 15% moderately undernourished, rest were normal. 54% children getting non formal preschool education. 64% mothers attending mothers’ meeting. 93% of 6 months to 3 years of children, 87% of 3-6 years of children and 100% of the pregnant and lactating mothers were getting supplementary nutrition. 47% adolescents availing the IFA/ deworming services. Kerosene used for cooking fuel. Conclusions: Few gaps identified related to growth monitoring, reporting of beneficiaries, delivering of some services. Those gaps need to be addressed for improved functioning of the AWC.